A Vida e Obra do Professor Doutor Manuel Cerqueira Gomes - Filipe André Jesus Ribeiro (2022)
Professor Manuel Cerqueira Gomes (1894-1973) was born in Braga and was a distinguished portuguese physician and professor at the Faculty of Medicine of the University of Porto. He obtained his medical degree at this faculty in 1918 and defended his doctoral thesis in 1921. After that, he studied electrocardiography in France, a method he introduced later in Portugal. He became a full professor of Medical Propaedeutics in 1957. He participated in several conferences in the Medical Pathology Department of Professor Gregório Marañon in Madrid. He was president of the Portuguese Medical Association, which he represented in international congresses, and a founder member of many portuguese medical associations. He was also a deputy in the Portuguese National Assembly, dealing with social and public health causes. Retired in 1964 from the academic services, he continued to practice private medicine in Porto until the end of his days. He died in 1973 and is remembered for his intelligence, clinical competence, dedication to teaching and public life, writing skills, oral skills, culture and humanism.